Study of dissolution nickel layer in enig surface finish during reflow soldering [electronic resource] - 177816 Wong, Mun Hon; Fakulti Kejuruteraan Mekanikal (Skudai : Universiti Teknologi Malaysia, 2006)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2006